Terminology applied in the study of user information when aimed at visually impaired people - Vieira da Silva Bastos, Karolina; Kafure Munoz, Ivette; Neves Raposo, Patrícia (Revista General de Información y Documentación, 2023)
Society comprises unique individuals; this is a human condition. Individuals think differently, act differently, and feel with varying intensities; and all this is because human beings live and make sense of the world in their own unique ways. Despite these differences, some terminologies help in expression and communication. From this perspective, this article aims to present the terminology for visually impaired people in the study of information users, based on the literature of information science and related areas. This is a qualitative study that uses a bibliographic method, associating conceptual aspects relevant to the topic. The study shows that terms and concepts should be defined for users with disabilities, and that user studies should be focused on people’s individuality and consider their experiences, needs, and expectations, thus paving the way for a holistic perspective.